Managerial Ability and Income Smoothing - Baik, Bok; Choi, Sunhwa; Farber, David B. (The Accounting Review, 2020)
ABSTRACT In this study, we investigate whether managerial ability is related to income smoothing and, if so, whether smoothing associated with managerial ability improves the informativeness of earnings and stock prices about future performance. Using a large sample of firms, we find that managerial ability is positively related to smoothing. More importantly, we show that high-ability managers incorporate more forward-looking information about cash flows into current earnings through smoothing, thereby enhancing earnings informativeness. We also find that smoothing associated with high-ability managers improves stock price informativeness about future cash flows. Our study should be of interest to researchers, practitioners, and others concerned with understanding the determinants and usefulness of smoothing.